2022
DOI: 10.1055/a-1898-4888
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Priming Exercise on Within-day Jumping Performance and its Relationship with Strength Level

Abstract: This study aimed to identify the effects of same day resistance priming exercise on countermovement jump parameters and subjective readiness, and to identify whether baseline strength level influenced these outcomes. Fourteen participants performed two separate conditions (Priming [2 sets high-load parallel squats with a 20% velocity loss cut-off] and Control) in a randomized, counterbalanced crossover design. Countermovement jump was assessed at pre, post and 6h while readiness was assessed at pre and at 6h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Limited findings suggest that strength qualities are associated with a heightened priming response. 6,10,22 These results support Eric's perception of the importance of strength qualities, 'Basically, from my knowledge, it's the stronger they are the more effective these sort of programs are going to be . .…”
Section: Consideration Of Athletes' Training Agesupporting
confidence: 60%
See 1 more Smart Citation
“…Limited findings suggest that strength qualities are associated with a heightened priming response. 6,10,22 These results support Eric's perception of the importance of strength qualities, 'Basically, from my knowledge, it's the stronger they are the more effective these sort of programs are going to be . .…”
Section: Consideration Of Athletes' Training Agesupporting
confidence: 60%
“…4 Although priming exercise has been shown to improve physical and perceptual responses, a number of studies have also found no change or significant decreases in these measures. [5][6][7]12,[14][15][16][22][23][24] Several factors may explain the lack of agreement in the literature. These include the training parameters used during a priming session, the duration separating the priming stimulus and subsequent performance, differences between exercise stimuli and testing measures researchers have utilised to assess performance and individual characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of movement was determined when a drop of 20 N from the baseline force (recorded during the weighing phase) was observed. Several variables derived from the force-time data were included in the reliability analysis because they may be of interest to strength and conditioning coaches for different reasons [7,13]. For intersession reliability the mean of the 3 jumps was used for analysis while intersession reliability was calculated with the 3 jumps of the first testing day.…”
Section: Methodsmentioning
confidence: 99%
“…This type of vertical jump-based testing is not only simple and time-efficient but has also proven to be sensitive to fatigue induced by exercise on the neuromuscular system in various sports [10,11]. For instance, the CMJ is capable of reflecting changes following both chronic [12] and acute training interventions [13][14][15]. Similarly, both the CMJ and the drop jump (DJ) have demonstrated being the two vertical jump tests that exhibit prolonged performance decrements post-exercise, suggesting an extended sensitivity compared to other tests such as the squat jump (SJ) or 20 m sprint times [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, previous studies have reported enhanced CMJ performance after low-volume/high-load squat protocols. 5 Similarly, González-García et al 28 reported that weaker participants (half squat relative = 1.76 1RM/kg of body weight) did not enhance CMJ height at any time point, while Chiu et al 16 suggested that the squat exercise could be a viable method to acutely enhance mechanical performance in athletic but not in recreationally trained individuals.…”
Section: Figurementioning
confidence: 99%